EAPH-14. MOLECULAR BIOLOGY AND PHASE I STUDY OF GM-CSF AND INTRATHECAL TRASTUZUMAB IN CHILDREN WITH RECURRENT POSTERIOR FOSSA EPENDYMOMA. Issue 2 (22nd June 2018) - Dorris, Kathleen; Widener, Melissa; Amani, Vladimir; Donson, Andrew; Schissel, Debra; O'Neill, Brent; Hankinson, Todd; Handler, Michael; Macy, Margaret; Foreman, Nicholas
Abstract: BACKGROUND: Posterior fossa ependymoma (PF EPN) is a pediatric central nervous system malignancy that has poor outcome to standard therapeutic approaches. The majority of PF EPN tumors have increased HER2 expression. Trastuzumab is a monoclonal antibody that targets HER2, and sargramostim (GM-CSF) stimulates hematopoietic progenitor cell proliferation. The combination of trastuzumab and GM-CSF has been shown to trigger antibody-dependent cell cytotoxicity in vitro in PF EPN cell lines. Due to reduced blood-brain barrier penetration of trastuzumab, intrathecal (IT) administration is an attractive method for delivery for treatment of recurrent PF-EPN. METHODS: Children aged 1–21 years with relapsed PF EPN and no CSF obstruction on imaging are eligible for the Phase I institutional trial at Children's Hospital Colorado. Stratum A involves IT trastuzumab and subcutaneous (subQ) GM-CSF prior to standard-of-care surgical resection. Stratum B involves a 3 + 3 phase I design with serial IT trastuzumab doses, each preceded by 3 days of GM-CSF, to establish the MTD for IT trastuzumab. RESULTS: Three patients (1:2; male:female) have been enrolled in Stratum A at trastuzumab Dose Level 1 (40 mg). Median age at enrollment is 8.8 years (range, 4.2–20.0 years). 2/3 tumors tested after pre-surgical trastuzumab and GM-CSF had detectable trastuzumab by mass spectroscopy. No adverse events at least possibly related to study therapy have occurred. CONCLUSIONS: IT trastuzumab penetrates PF EPN tumor tissue. Stratum A remains open to enrollment for eligible patients who have clinical indication for surgical resection. Based on Stratum A results, Stratum B is now also open to accrual.